2023
DOI: 10.3390/diagnostics13152476
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Paxillin Expression in Epithelial Dysplasia, Oral Squamous Cell Carcinoma, Lichen Planus with and without Dysplasia, and Hyperkeratosis: A Retrospective Cross-Sectional Study

Abstract: Background: Paxillin is a cytoskeletal protein involved in the pathogenesis of several types of cancers. However, the roles of paxillin in epithelial dysplasia (ED), oral squamous cell carcinoma (OSCC), oral lichen planus with dysplasia (OLPD), hyperkeratosis (HK), and oral lichen planus (OLP) have remained unnoticed in the literature. This study aimed to evaluate its attainable functions in the pathogenesis and malignant transformation of potentially malignant oral epithelium and benign lesions. Methods: In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…34 Meanwhile, several studies have indicated that Paxillin is involved in the regulation of endothelial cell proliferation, migration and angiogenesis. 35,36 Overexpression of CDC42 in BM-MSCs cells detected the expression of intracellular PAK1. We found that the expression of PAK1 was significantly elevated in cells overexpressing CDC42 compared to cells transfected with si-MALAT1.…”
Section: Discussionmentioning
confidence: 99%
“…34 Meanwhile, several studies have indicated that Paxillin is involved in the regulation of endothelial cell proliferation, migration and angiogenesis. 35,36 Overexpression of CDC42 in BM-MSCs cells detected the expression of intracellular PAK1. We found that the expression of PAK1 was significantly elevated in cells overexpressing CDC42 compared to cells transfected with si-MALAT1.…”
Section: Discussionmentioning
confidence: 99%
“…P21-activated kinase-1 (PAK1) is an important effector protein of CDC42 and is closely related to cell motility [ 41 ]. Several studies have indicated that paxillin is involved in the regulation of endothelial cell proliferation, migration, and angiogenesis [ 42 , 43 ]. In the present study, PAK1 expression was significantly elevated in cells with simultaneous overexpression of CDC42 and inhibition of MALAT1 compared to cells with only MALAT1 inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Oral health plays a significant role in maintaining general health [1,2]. Oral squamous cell carcinoma (OSCC) is the prevailing malignant tumor among all types of squamous cell carcinomas that occur in the head and neck region [3], ranking 18th globally in 2018 [4,5]. OSCC is known for its propensity to recur, metastasize, and invade local tissues [6].…”
Section: Introductionmentioning
confidence: 99%